Safety and effectiveness of standardized exercise training in patients with pulmonary hypertension associated with heart failure with preserved ejection fraction (TRAIN-HFpEF-PH): study protocol for a randomized controlled multicenter trial - Palevičiūtė, Eglė; Čelutkienė, Jelena; Šimbelytė, Toma; Gumbienė, Lina; Jurevičienė, Elena; Zakarkaitė, Diana; Čėsna, Sigitas; Eichstaedt, Christina; Benjamin, Nicola; Grünig, Ekkehard (Trials, 2023)
Left heart failure (HF) is characterized by an elevation in left-sided filling pressures, causing symptoms of dyspnea, impairing exercise capacity, and leading to pulmonary venous congestion and secondary pulmonary hypertension (PH). There is an increased incidence of PH associated with left heart disease, particularly with heart failure with preserved ejection fraction (HFpEF-PH). Treatment possibilities in HFpEF-PH are non-specific and very limited, thus additional pharmacological and non-pharmacological therapeutic strategies are needed. Various types of exercise-based rehabilitation programs have been shown to improve exercise capacity and quality of life (QoL) of HF and PH patients. However, no study focused on exercise training in the population of HFpEF-PH. This study is designed to investigate whether a standardized low-intensity exercise and respiratory training program is safe and may improve exercise capacity, QoL, hemodynamics, diastolic function, and biomarkers in patients with HFpEF-PH.